2017
DOI: 10.1016/j.jallcom.2017.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer design of CrN/MoN protective coatings for enhanced hardness and toughness

Abstract: We report on CrN/MoN multilayer coatings, their structure, elemental and phase composition, residual stresses, mechanical properties and their dependence on deposition conditions. The hardness and toughness were considered as main parameters for improvement of the protective properties of coatings. Multilayers with varying bilayer periods, ranging from 40 nm to 2.2 mm, were obtained by using cathodic arc physical vapour deposition (Arc-PVD) on stainless steel substrate. The elemental analysis was performed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 53 publications
2
31
0
Order By: Relevance
“…Recently, CrN/MoN coating has been deposited on 12X18H9T stainless steel using Vacuum arc evaporation method by Pogrebnjak et al [109]. Multilayers of chromium and molybdenum are believed to induce the high value of hardness [110][111][112][113][114][115][116], and the observation on the well-defined multilayer structure of this study confirms it. The coating exerts high hardness value at 42.3 GPa, due to Hall-Petch strengthening mechanism.…”
Section: Hybridsupporting
confidence: 76%
“…Recently, CrN/MoN coating has been deposited on 12X18H9T stainless steel using Vacuum arc evaporation method by Pogrebnjak et al [109]. Multilayers of chromium and molybdenum are believed to induce the high value of hardness [110][111][112][113][114][115][116], and the observation on the well-defined multilayer structure of this study confirms it. The coating exerts high hardness value at 42.3 GPa, due to Hall-Petch strengthening mechanism.…”
Section: Hybridsupporting
confidence: 76%
“…Figure 11, where the light lines correspond to MoN and the dark ones correspond to TiN layers [120,125]. It may be caused by different time evaporation of cathodes and deposition rates of nitride layers [126]. TEM studies of TiN/MoN coatings showed a growth of the columnar structure ( Figure 12).…”
Section: Structure Phase Composition Mechanical and Tribological Prmentioning
confidence: 99%
“…On the other hand, the design of multilayer coatings with different composition of bilayers (soft and solid phases) allows to reduce internal stresses and brittleness while high values of hardness from 30 to 45 GPa are maintained [18][19][20][21][22][23][24][25][26][27][28]. One of the promising multilayer systems is the combination of chromium and molybdenum nitrides [29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%